(untitled) (International journal of artificial intelligence, 2026)
This article presents a scientific analysis of issues related to assessing population physical fitness levels and developing mass sports. The research, based on contemporary literature analysis, demonstrates the role of physical activity and mass sports events in strengthening population health. The results show that systematic physical exercises and mass sports events are of significant importance in improving population health, increasing social wellbeing, and enhancing national health indicators.